Central nervous system neurons migrate on astroglial fibers from heterotypic brain regions in vitro. - Gasser, U E (1990)
In different regions of the developing mammalian brain, neurons follow the processes of radial glial cells over very different trajectories to reach their destinations in specific neuronal layers. To investigate whether the movement of neurons along glial fibers is specified by glia in a given region or whether glia provide a permissive substrate for migration in different brain regions, we purified neurons and astroglial cells from developing cerebellum and hippocampus and analyzed neuronal migration on heterotypic glial fibers with time-lapse, video-enhanced differential interference microscopy in vitro. Granule neurons purified from early postnatal rat cerebellum migrated on astroglial processes of glia purified from late embryonic or early postnatal rat hippocampus with a cytology, neuron-glial relationship, and dynamics of movement that were indistinguishable from those of mouse granule cells migrating on cerebellar astroglial processes in vitro [Edmondson, J. C. & Hatten, M. E. (1987) J. Neurosci. 7, 1928-1934]. In the reciprocal combination, hippocampal neurons migrated on cerebellar glial processes in a manner that was also remarkably similar to migration along homotypic, hippocampal glial fibers [Gasser, U. E. & Hatten, M. E. (1990) J. Neurosci. 10, 1276-1285]. In all cases, migrating neurons had a characteristic appearance, apposing their cell soma against the glial fiber and extending in the direction of migration a motile, leading process that enfolded the glial fiber with short filopodia and lamellipodia. As seen by video microscopy, neurons moved along homotypic and heterotypic glial processes by translocation of the soma and were not "pulled" forward by the leading process. As the neuron moved, the nucleus remained in the posterior portion of the cell and cytoplasmic vesicles moved forward from the soma into the leading process. The dynamics of the movement of neurons along heterotypic glial substrates, including the speed and periodicity of motion, was identical to that of neurons migrating along homotypic glial substrates. These experiments suggest that the mechanism of movement of neurons along glial fibers is conserved in these two brain regions during development.